The landscape of bispecific T cell engager in cancer treatment - Shujie Zhou; Mingguo Liu; Fei Ren; Xiangjiao Meng; Jinming Yu (BMC, 2021)
Abstract T cell-based immunotherapies have revolutionized treatment paradigms in various cancers, however, limited response rates secondary to lack of significant T-cell infiltration in the tumor site remain a major problem. To address this limitation, strategies for redirecting T cells to treat cancer are being intensively investigated, while the bispecific T cell engager (BiTE) therapy constitutes one of the most promising therapeutic approaches. BiTE is a bispecific antibody construct with a unique function, simultaneously binding an antigen on tumor cells and a surface molecule on T cells to induce tumor lysis. BiTE therapy represented by blinatumomab has achieved impressive efficacy in the treatment of B cell malignancies. However, major mechanisms of resistance to BiTE therapy are associated with antigen loss and immunosuppressive factors such as the upregulation of immune checkpoints. Thus, modification of antibody constructs and searching for combination strategies designed to further enhance treatment efficacy as well as reduce toxicity has become an urgent issue, especially for solid tumors in which response to BiTE therapy is always poor. In particular, immunotherapies focusing on innate immunity have attracted increasing interest and have shown promising anti-tumor activity by engaging innate cells or innate-like cells, which can be used alone or complement current therapies. In this review, we depict the landscape of BiTE therapy, including clinical advances with potential response predictors, challenges of treatment toxicity and resistance, and developments of novel immune cell-based engager therapy.